Oxytocin selectively biases sensory–prefrontal communication through network-level suppression and theta coupling - DaYoung Jung; Hio-Been Han; Jungyoung Kim; Ji Hyung Kim; Robert C. Froemke; Jee Hyun Choi (Proceedings of the National Academy of Sciences, 2026)
Oxytocin modulates social information processing by altering excitatory-inhibitory balance at the microcircuit level, but how such local modulation gives rise to selective processing at the level of distributed brain systems remains unclear. Here, we investigated the effects of oxytocin on large-scale neurodynamics across cortico-limbic network in the mouse brain using multisite local field potential recordings. Oxytocin selectively enhanced neural responses to infant calls in the auditory cortex (AC) and medial prefrontal cortex (mPFC). These enhancements occurred while baseline activity was reduced, indicating increased signal-to-noise ratio rather than a global increase in excitability. During auditory steady-state responses (ASSRs), oxytocin increased prefrontal phase coherence without altering ASSR power. During rest, oxytocin induced a transient, broadband reduction in spontaneous spectral power across regions. Despite this reduction in activity, analyses of interregional interactions revealed a selective increase in low-theta phase coupling and directional connectivity of AC→mPFC. Session-level analyses showed that stronger bottom–up AC→mPFC coupling was associated with lower prefrontal power, consistent with a gating or disinhibitory network regime favoring sensory-to-prefrontal information transfer. Multivariate analyses showed that oxytocin/saline conditions were reliably discriminable using supervised classification models, with specific contributions from spectral power, phase-locking, and Granger-causal connectivity features. Conversely, unsupervised dimensionality reduction did not identify a distinct low-dimensional manifold separating conditions, although a modest shift in the centroid of neural state space was observed. Together, these results indicate that oxytocin reduces background neural activity while selectively enhancing sensory–prefrontal network interactions, providing a systems-level account linking local inhibitory modulation to selective processing of socially salient infant cues.